Postpartum Depression in Urban India: A Pilot Study from Prayagraj District, India - Shivangi R Kiran; Ritu K. Sureka (Journal of Asian Social Science Research, 2026)
Abstract Postpartum depression (PPD) affects maternal well-being, infant care, and family functioning. In India, however, postpartum mental health services remain limited, while evidence from urban North India is still insufficient, particularly regarding the influence of household relationships, reproductive expectations, and psychosocial support. This pilot study aimed to estimate PPD risk and examine associated sociodemographic, obstetric, psychosocial, and cultural factors among postpartum women in Chak Dondi, Naini, Prayagraj. Using a cross-sectional design, 30 women within six months of delivery were selected through purposive sampling. Data were collected using the Edinburgh Postnatal Depression Scale and a structured questionnaire, then analysed through descriptive statistics and exploratory bivariate tests. Findings show that 23.3% of participants screened positive for possible PPD. Higher risk was associated with younger age, financial dependence, nuclear family structure, psychiatric history, unplanned pregnancy, obstetric complications, son preference, domestic violence, strained family relationships, and limited in-law support, while family support appeared protective. The study contributes preliminary evidence from an under-researched urban North Indian setting. Its findings support integrating routine screening, counselling, referral, and family-centred support into maternal healthcare. Given the small purposive sample, larger studies are required to confirm these patterns.